1996
DOI: 10.1016/0735-1097(95)00433-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of hemostatic predictors of subacute stent thrombosis after coronary palmaz-schatz stenting

Abstract: Platelet fibrinogen receptor expression is an independent predictor of subacute stent occlusion. However, fibrinogen and F1 + 2 concentrations do not show a strong relation to the risk of stent occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 35 publications
1
39
0
1
Order By: Relevance
“…61 Tschoepe and colleagues 41 found that an increased fraction of platelets surface expressing P-selectin or thrombospondin is predictive for occurrence of ischemic events after PTCA. We 43,62 showed that GP IIb/IIIa levels before stenting were an independent risk factor for stent thrombosis (Figure 12). …”
Section: Platelet Analysis and Risk Stratificationmentioning
confidence: 99%
“…61 Tschoepe and colleagues 41 found that an increased fraction of platelets surface expressing P-selectin or thrombospondin is predictive for occurrence of ischemic events after PTCA. We 43,62 showed that GP IIb/IIIa levels before stenting were an independent risk factor for stent thrombosis (Figure 12). …”
Section: Platelet Analysis and Risk Stratificationmentioning
confidence: 99%
“…Neuman et al 3 have shown that the level of platelet glycoprotein (GP) IIb/IIIa expression was an independent predictor of stent thrombosis. According to the European Society of Cardiology guidelines, 4 the use of GP IIb/IIIa inhibitors (GPIs) is reasonable as bailout therapy in the event of angiographic evidence of large thrombus, slow or no reflow, and other thrombotic complications.…”
mentioning
confidence: 99%
“…Another strategy to limit reperfusion injury uses monoclonal antibodies to adhesion receptors such as p selectin (present on endothelial cells and PLTs), CD11/CD18 (present on leukocytes), and the vitronectin receptor (present on endothelial cells). Abciximab not only blocks GP IIb-IIIa on PLTs, but also the vitronectin receptor on endothelial cells explaining its favorable effect on myocardial perfusion, microcirculation, and recovery of left ventricular function [14][15][16][17].…”
Section: Plt-mediated Inflammationmentioning
confidence: 99%